2017
DOI: 10.1002/adfm.201700406
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in Shape and Ligand‐Conjugation of Hybrid Nanoparticulates Manipulates the Mode of Bio–Nano Interaction and Its Outcome

Abstract: In an attempt to manipulate the biological features of nanomaterials via both anisotropic shape and ligand modification, four types of nanoparticulates with good morphological stability are designed and engineered, including hybrid nanospheres, nanodiscs, and nanodiscs with edge modification or plane modification of octa-arginine (R8) sequence. It is found that the R8 modification anisotropy can trigger huge differences in the endocytosis, intracellular trafficking, and even tissue penetration of nanoparticula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…Shapeand surface-anisotropic colloids [1] are currently in high demand, as their directional properties are beneficial for hierarchical self-assembly, [2] locomotion, [3] active structuring, [4] interfacial activity, [5] and drug delivery. [6,7] Amongst the conceivable shapes,b owl or cup-shaped particles are as pecial case that combines an anisotropic shape with an open cavity.O wing to their shape,g old nanocups show multiple plasmon resonances and serve as metallodielectric nanoparticles. [8][9][10][11] Cups demonstrate distinct self-assembly behavior through shape-recognition leading to precise colloidal molecules, [12] 1D self-assemblies, [13] or non-classical packing in colloids crystals.…”
mentioning
confidence: 99%
“…Shapeand surface-anisotropic colloids [1] are currently in high demand, as their directional properties are beneficial for hierarchical self-assembly, [2] locomotion, [3] active structuring, [4] interfacial activity, [5] and drug delivery. [6,7] Amongst the conceivable shapes,b owl or cup-shaped particles are as pecial case that combines an anisotropic shape with an open cavity.O wing to their shape,g old nanocups show multiple plasmon resonances and serve as metallodielectric nanoparticles. [8][9][10][11] Cups demonstrate distinct self-assembly behavior through shape-recognition leading to precise colloidal molecules, [12] 1D self-assemblies, [13] or non-classical packing in colloids crystals.…”
mentioning
confidence: 99%
“…It is impossible in the simulation to create a liposome and bicelle with an identical lipid number. Following the idea in experiments, 29,31 the liposome and bicelle are assumed to have the same size, around R = 11r 0 (as denoted in Fig. 1), in our simulations.…”
Section: Computational Model and Methodsmentioning
confidence: 99%
“…26 Furthermore, compared with liposomes, bicelles are found to have a better chance to be internalized by tumor cells. For example, Wang et al 29 compared the cellular uptake of bicelles and liposomes with the modification of the octa-arginine (R8) sequence in four different cell lines, including MM-231, human breast cancer cell MCF-7, human umbilical vein endothelial cell HUVEC and murine macrophage cell RAW264.7. They found that bicelles are more efficiently internalized by all these cells.…”
Section: Introductionmentioning
confidence: 99%
“…2 For instance, nanoparticles with a larger aspect ratio were observed to be internalized at a faster rate and higher frequency. 3,4 This indicates that cell internalization could be controlled via rational design and fabrication of nanoparticles with well-defined characteristics.…”
Section: Introductionmentioning
confidence: 99%